Sampling and conceptualization in Grounded Theory - Conlon, Catherine (Sage, 2020)
Grounded theory (GT) follows symbolic interactionism in viewing humans as active agents in their own lives who create meaning in the processes of action and interaction. GT thus proffers that theory can be discovered in empirical data. This approach originates from a realist ontology positing that theoretical accounts of processes reside in data to be discovered by the researcher, independent of the researcher. Glaser and Strauss (1967) first outlined GT in 1967 in response to a social science they considered to be dominated by deduction (see the lengthier discussion on this in Chapter 10). The core premise of GT is that there are regularities to the social world out there, which the researcher can locate through systematic observation and analysis of human action and interaction. The inductive emphasis of GT challenges the prevailing model of research based on deductive hypothesis testing. Since then researchers have proposed different variations of GT reflecting ontological and epistemological debates and turns in the intervening time. Concerns regarding the place of the researcher in social inquiry are attended to by Strauss and Corbin (1998) and Corbin and Strauss (2015) who deal with issues of reflexivity in a GT inquiry. Charmaz (2006, 2014) goes further and develops GT in conversation with a social constructivist perspective. Her approach re-situates the researcher as fully implicated in all stages of the inquiry and she argues that what emerges are portrayals as opposed to universalist, singular theoretical account. Clarke (2014) similarly addresses concerns about context and proposes a situational analysis approach premised on the position that any condition is situation-specific, which is why context as well as process should be investigated. More recently, the realist origins of the method have been taken up again by researchers working within a critical realist perspective (e.g., Kempter and Parry, 2011, 2014; Lee, 2016; Oliver, 2012). This recent branch of research asserts that even though reality is a phenomenon existing ‘out there’, the meaning of reality is specific to individuals and contexts and therefore fluid (for a further account of how the method evolved, see Chapter 10, pp. 000–000). This chapter illustrates the use of GT in practice using the example of an inquiry entitled Changing Generations (see Timonen et al., 2013; Conlon et al., 2015). This study is concerned with intergenerational solidarity in Ireland in the period following the ‘great recession’ that began in 2008. The study’s data set comprises qualitative interviews. My approach is inspired by Charmaz’s constructivist iteration of GT. However, I illustrate the generic processes of GT as well as its inflection in a constructivist approach. The emergent nature of GT is illustrated in the chapter through the following characteristics: the imperative to remain open; the iterative nature of GT achieved through theoretical sampling; the use of memos in GT; and the constant comparative procedures revealing processes in the data giving way to theory-building.
Qualitative analysis eight approaches
PUBLISHED
London
Keywords: Inclusive Society; Inclusive research; Intergenerational Solidarity